2000
DOI: 10.1046/j.1444-2906.2000.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dietary protein sources on tissue free amino acid levels of fingerling rainbow trout

Abstract: SUMMARY: To estimate the quantitative adequacy of amino acids in practical dietary proteins, free amino acid (FAA) levels in various tissues of rainbow trout Oncorhynchus mykiss fed different protein sources were compared. Four diets, the proteins of which were derived mainly from fish meal (FM diet), soybean meal (SBM diet), malt protein flour (MPF diet), and the combination of SBM and MPF (COMB diet), were fed to duplicate groups (30 fish/group, 10 g/fish) for 6 to 9 weeks at 15°C, until each treatment group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…It has been reported that taurine is rich in FM and poor in plant protein sources including soybean [27], and taurine supplementation markedly improved growth performance of yellowtail fed with soy protein concentrate-based diets [11,28]. In the present study, however, tissue taurine contents did not differ among fish fed with SBM, SPI, DSPI, and DPSPI, and were lower than those of fish fed with FM (Fig.…”
Section: Discussioncontrasting
confidence: 81%
“…It has been reported that taurine is rich in FM and poor in plant protein sources including soybean [27], and taurine supplementation markedly improved growth performance of yellowtail fed with soy protein concentrate-based diets [11,28]. In the present study, however, tissue taurine contents did not differ among fish fed with SBM, SPI, DSPI, and DPSPI, and were lower than those of fish fed with FM (Fig.…”
Section: Discussioncontrasting
confidence: 81%
“…15 This indicated that taurine is the sole amino acid that is conjugated with bile acid to produce the taurocholic acid or taurochenodeoxycholic acid in the liver of fish. 16 Yamamoto et al 17 reported that tissue taurine levels of the high fat diet group were generally lower than the low fat diet group in rainbow trout. Bile acids are conjugated with taurine that serve to solubilize SK Kim et al or emulsify fats to make them more accessible for digestion.…”
Section: Resultsmentioning
confidence: 99%
“…In fish, levels of FAA in tissues are known to be affected by dietary protein quality (Dabrowska ; Cowey, Walton & Halver ; Yamamoto, Unuma & Akiyama ). In the present study, the total free amino acids levels of hepatopancreas were significantly increased with dietary taurine level.…”
Section: Discussionmentioning
confidence: 99%